Differences in Verbal Aggression Based on the Argumentativeness Trait in Social Media Users - Mutmainna, A. Sri; Daud, Muh.; Hamid, Andi Nasrawaty (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Verbal aggression is a common phenomenon in online interactions and may vary depending on individual differences in trait argumentativeness. This study aims to examine the differences in verbal aggression based on trait argumentativeness among social media users. The participants were 504 social media users aged 18 years and above, recruited through accidental sampling. The research employed the Verbal Aggression Scale and the Trait Argumentativeness Scale as measurement instruments. Based on the trait argumentativeness scores, respondents were categorized into three groups: high, moderate, and low argumentativeness. Data were analyzed using non-parametric statistics with the Kruskal–Wallis test. The results indicated a significant difference in verbal aggression across the three groups (p = 0.001, p < 0.05). Post Hoc Dunn’s tests revealed that the high argumentativeness group significantly differed from both the moderate (p = 0.001) and low argumentativeness groups (p = 0.001). However, no significant difference was found between the moderate and low argumentativeness groups (p = 0.496, p > 0.05). The findings suggest that individuals characterized by higher levels of trait argumentativeness are more likely to display greater verbal aggression on social media than those with lower levels.